PENERAPAN MODEL PEMBELAJARAN SNOWBALL THROWING UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN IPS PADA SISWA KELAS V SDN KALIBANTENG KIDUL 01 KOTA SEMARANG (APLICATING SNOWBALL THROWING MODEL FOR IMPROVING THE SOCIAL INTRUCTIONAL AT FIFTH, SDN KALIBANTENG KI (Jurnal Kreatif : Jurnal Kependidikan Dasar, 2011)
Based on preliminary data which were obtained through the observations first grade of SDN Kalibanteng Kidul 01, Semarang city was found some problems in learning processes. The less maximum of the teacher in using 8 teaching skill impact on not maximum of student activities. The lack of variety and innovation in learning processes to make the students do actvities that are inconsistent with learnin. It is an impact on students’activity and result learning. Formulation of the problem in this study were: (1) Does model of Snowball Throwinglearning can improve the teacher skill in learning processes of SDN Kalibanteng Kidul 01 Semarang city? (2) Does model  Snowball Throwing learning can improve students’ activities in learning processes of SDN Kalibanteng Kidul 01 Semarang city? (3)Does model Snowball Throwinglearning can improve learning quality of SDN Kalibanteng Kidul 01 Semarang city? The research goals of this class action are: (1) To increase the teachers’ skills by applying the model of Snowball Throwing. (2) To increase the students’ activities in learning by applying the model ofSnowball Throwing. (3) To increase learning quality by applying the model of Snowball Throwing. This research is classroom action research using a model of Snowball Throwinglearning. It counsist of  three cycles. Each cycle consists of four stages, namely planning, execution, observations and reflection. The subject of this research were the teachers and the students on fifth  grade of SDN Kalibanteng Kidul 01 Semarang city. Data collection techniques using the test techniques, observation, documentation and The result showed that the teacher’s skill has increassed. On first cycle the teachers’ skill get a score with average 2,5 which included in good category. On second cycle the techers’ skill get score with average 3,4 which included in very good category. On third scycle the techers’ skill get score with average3,4 which included in very good category.The increase also occured in students activities. On first cycle the students activities get score with average 3,0 which included in good category, and on second cycle the students activities get score with average 3,53 which included in very good category. and on third cycle the students activities get score with average 3,56 which included in very good category. On first cycle the learning result getaverage 67,6 with percentage 63% students is success in learning., on second cycle the learning result increasing get average 73,5 with persentagen73,9% students  is success in learning. On third cycle the learning result get average 76,5 with percentage 84,7% students is successin learning. This shows that percentage of learning result 80% so is success full. Conclusion from classroom action research by model of Snowball Throwing learning can be increase teacher skill in learning IPS. To increase the students’ activities in learning by applying the model ofSnowball Throwing. (3) To increase learning quality by applying the model of Snowball Throwing. Model of Snowball Throwing can be implemented to increase learning result. Keywords: Snowball Throwing learning, quality learning  IPS